Comparison of data correction methods for blockage effects in semispan wing model testing - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin (EDP Sciences, 2016)
Wing alone models are usually tested in wind tunnels for aerospace applications like aircraft and hybrid buoyant aircraft. Raw data obtained from such testing is subject to different corrections such as wall interference, blockage, offset in angle of attack, dynamic pressure and free stream velocity etc. Since the flow is constrained by wind tunnel walls, therefore special emphasis is required to deliberate the limitation of correction methods for blockage correction. In the present research work, different aspects of existing correction methods are explored with the help of an example of a straight semi-span wing. Based on the results of analytical relationships of standard methods, it was found that although multiple variables are involved in the standard methods for the estimation of blockage, they are based on linearized flow theory such as source sink method and potential flow assumption etc, which have intrinsic limitations. Based on the computed and estimated experimental results, it is recommended to obtain the corrections by adding the difference in results of solid walls and far-field condition in the wind tunnel data. Computational Fluid Dynamics technique is found to be useful to determine the correction factors for a wing installed at zero spacer height/gap, with and without the tunnel wall.